2015
DOI: 10.1161/circulationaha.115.017168
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex on Long-Term Outcomes After Implantation of Bare-Metal Stent

Abstract: Background-Female sex was reported to be associated with lower risk for midterm restenosis and repeat revascularization after bare-metal stent implantation. However, the influence of sex on very long-term outcomes after bare-metal stent implantation has not been yet reported. Methods and Results-Among the 9877 patients in the multicenter Coronary Revascularization Demonstrating Outcome study in Kyoto (CREDO-Kyoto) registry cohort-1, bare-metal stent implantation was performed in 5313 patients (men, n=3742 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…23 In the present study, clinical outcomes after CABG were also better in women compared with men except for stroke. Therefore, there was no significant sex-related difference in the effect of PCI relative to CABG for mortality, MI, HF hospitalization, and any Figure 4.…”
Section: Discussionsupporting
confidence: 55%
“…23 In the present study, clinical outcomes after CABG were also better in women compared with men except for stroke. Therefore, there was no significant sex-related difference in the effect of PCI relative to CABG for mortality, MI, HF hospitalization, and any Figure 4.…”
Section: Discussionsupporting
confidence: 55%
“…However, it has been reported that 18.3% of patients with post-myocardial infarction in European countries experienced some cardiovascular events within 1 year, 17 and 23.0% of patients undergoing drug-eluting stent implantation in Japan experienced non-target lesion revascularization within 5 years. 18 Therefore, CR, including disease management and behavioral changes for a healthier lifestyle, is highly recommended. 5 In addition, due to increases in the aging population and technological advances in medicine and surgery, the number of elderly patients undergoing cardiovascular (CV) surgery is gradually increasing.…”
mentioning
confidence: 99%
“…However, there are problems such as immune reaction, formation of thrombus, stress masking around the implant, difficulty in revision surgery, and implant-related infection or fracture, which cause great pain to patients [4][5]. Therefore, the concept of degradable metallic implant materials, which can be gradually corroded by body fluids in vivo and completely dissolved during tissue healing, was proposed [6][7][8]. In this process, the load is gradually transferred to the healing tissues without the need for secondary surgical removal, which reduces patients' pain and the risk of secondary surgery and medical costs.…”
Section: Introductionmentioning
confidence: 99%